2016
DOI: 10.1002/clen.201500628
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Nanomaterials on the Metabolic Activity and Bacterial Flora of Activated Sludge Medium

Abstract: In this study, the dominant and representative bacteria of activated sludge before and after the addition of different nanomaterials (NMs) (multiwalled carbon nanotube, MWCNT, silicon dioxide nanoparticle, nSiO 2 , titanium oxide nanoparticle, nTiO 2 , aluminum oxide-nanoparticle, nAl 2 O 3 , and silver nanoparticle, nAg) were separately isolated, enumerated, and identified. In total, 17 different representative isolates were identified by using 16S rDNA gene sequence analysis. The effects of NMs on the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Button et al [ 216 ], for instance, did not detect any negative effects on microbial community structure and function in wetland systems when exposed for 28 days to ionic Ag, citrate- and PVP-coated Ag NP (at 100 µg/L). These microbial communities, however, developed an Ag resistance, indicating an existing potential to adapt to such emerging stressors by elevating the production of extracellular polymers [ 217 ], while the costs of this adaptation remain unclear. Evidence is increasing that nitrifiers are among the most sensitive microorganisms towards Ag NP [ 218 220 ], even when the NP are sulfidized [ 88 ].…”
Section: Np Effects In Communities and Consequences For Trophic Intermentioning
confidence: 99%
“…Button et al [ 216 ], for instance, did not detect any negative effects on microbial community structure and function in wetland systems when exposed for 28 days to ionic Ag, citrate- and PVP-coated Ag NP (at 100 µg/L). These microbial communities, however, developed an Ag resistance, indicating an existing potential to adapt to such emerging stressors by elevating the production of extracellular polymers [ 217 ], while the costs of this adaptation remain unclear. Evidence is increasing that nitrifiers are among the most sensitive microorganisms towards Ag NP [ 218 220 ], even when the NP are sulfidized [ 88 ].…”
Section: Np Effects In Communities and Consequences For Trophic Intermentioning
confidence: 99%
“…[114] A recent study showed that nanomaterials such as CNTs, TiO2, SiO2 and Al2O3 nanoparticles influence bacterial respiration and production of extracellular polymeric substances. [115] Experimental and molecular dynamic simulation analyses demonstrated that CNT can enhance direct EET in S. oneidensis by developing a strong electronic conduit with OM c-Cyts (Figure 10B). [116] Cell-secreted flavin mediated EET process is usually dominated in S. oneidensis.…”
Section: Rational Design Of High-performing Ccphf Cathodes For Mesmentioning
confidence: 99%
“…One of the major problems of MBRs is membrane biofouling which causes the flux decline and increases the unit cost of wastewater treatment (Drews, 2010;Lade et al, 2014;Wu and Fane, 2012). Various studies have considered the effect of membrane modification with nanoparticles (Koseoglu-Imer et al, 2013;Rahimi et al, 2015;Ergön-Can et al, 2016) and the effect of the varying operating conditions (Ahmed et al, 2007;Wu et al, 2011;Dvorak et al, 2011) in order to prevent and/or mitigate the biofouling. However, biological-based biofouling mitigation techniques have come forward due to the high costs and instability of the physical and chemical-based approaches.…”
Section: Introductionmentioning
confidence: 99%